5(x-9)-7(3+6)=25

Simple and best practice solution for 5(x-9)-7(3+6)=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-9)-7(3+6)=25 equation:


Simplifying
5(x + -9) + -7(3 + 6) = 25

Reorder the terms:
5(-9 + x) + -7(3 + 6) = 25
(-9 * 5 + x * 5) + -7(3 + 6) = 25
(-45 + 5x) + -7(3 + 6) = 25

Combine like terms: 3 + 6 = 9
-45 + 5x + -7(9) = 25

Multiply -7 * 9
-45 + 5x + -63 = 25

Reorder the terms:
-45 + -63 + 5x = 25

Combine like terms: -45 + -63 = -108
-108 + 5x = 25

Solving
-108 + 5x = 25

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '108' to each side of the equation.
-108 + 108 + 5x = 25 + 108

Combine like terms: -108 + 108 = 0
0 + 5x = 25 + 108
5x = 25 + 108

Combine like terms: 25 + 108 = 133
5x = 133

Divide each side by '5'.
x = 26.6

Simplifying
x = 26.6

See similar equations:

| 5(x-9)-73(x+6)=25 | | (7x-9)+(4x+22)=90 | | 8-2x+3=3x+11-5x | | X+(-3)=-12 | | 0.64=0.8 | | 6y=2x-9 | | h(t)=-16t^2+50t+9 | | 5=2/x-7 | | 181-u=285 | | 15x^2-34x-33=0 | | y=0.2(x-8)+2.8 | | 4-3x=9x | | 24x^3-16x^2=68x | | 2=-8v+5(v-2) | | x(x(x+1)+-4)=-2 | | 1.5=x*(1.65)+(1-x)*2 | | x(x(x+1)+-4)=-1 | | 26+3(16+24)-y=123 | | -4z+16=-6z | | x(x(x+1)-4)+10=0 | | -4z+16=-6x | | 1.5=x*(1.65)+(1-x)*0 | | 3/4(z-1)=-2/3(z-2) | | 4x^3-81y=0 | | A=X^2+15X+50 | | 6w+16=-v+16 | | Z+71=135 | | 4(17)+9= | | 4x+7x+9-18=180 | | -13-(-14/(6-(-4)-(-1) | | 7(20.25)-18= | | 7(20.25)-18=90 |

Equations solver categories